Multiple hepatic sclerosing hemangiomas: a case report and review of the literature - Kyohei Yugawa; Tomoharu Yoshizumi; Noboru Harada; Takashi Motomura; Norifumi Harimoto; Shinji Itoh; Toru Ikegami; Yuji Soejima; Yoshihiko Maehara (Surgical Case Reports)
Abstract Background Hepatic sclerosing hemangioma, a very rare benign tumor, is characterized by fibrosis and hyalinization occurring in association with degeneration of a hepatic cavernous hemangioma. Such atypical hemangiomas can be diagnosed incorrectly as primary or metastatic malignancies based on imaging characteristics. We present herein a rare case of giant and multiple hepatic sclerosing hemangiomas that are difficult to differentiate from hepatic malignancies and review the relevant literature. Case presentation The patient was a 48-year-old male who was found to have multiple hepatic tumors and a giant tumor (67 × 53 mm) superior to the inferior vena cave by an abdominal ultrasonography during a routine medical examination. The patient was referred to our hospital for further evaluations and diagnosis of the multiple hepatic tumors. Dynamic CT showed low-density tumors in the delayed phase suggestive of membrane-covered lesions. EOB-MRI demonstrated a mass with low-signal intensity mass on T1-weighted images and areas of high-signal intensity on T2-weighted images and a hypointense mass in the hepatobiliary phase, which showed high intensity on DWI-based ADC map. FDG-PET showed no accumulation of [18F]-FDG. A provisional diagnosis of multiple scirrhous hepatocellular carcinomas was made on the basis of these imaging studies, and caudate lobectomy of the liver and partial hepatectomy of S2 and S6 were performed. Histopathological examination showed that the tumors were composed of various sized irregularly dilated vessels with some blood thrombi, inflammatory cell infiltration, fibrous and hyalinized sclerotic or myxomatous stroma, resulting in a diagnosis of multiple hepatic sclerosing hemangiomas. Conclusions Differentiation of multiple sclerosing hemangiomas from other hepatic malignant tumors, such as intrahepatic cholangiocarcinoma, metastatic liver cancer, and scirrhous hepatocellular carcinoma characterized by abundant fibrous stroma, is difficult because the radiological findings are very similar. Inclusion of hepatic sclerosing hemangioma in the differential diagnosis of multiple liver tumors could enable optimal management; this possibility is important to consider before planning invasive therapies.